Voice Content and Usability - So, Preston (A Book Apart, 2021)
Interfaces have long been visual affairs, with content confined to the text and images behind our screens. But thatâ??s changing. Humans have started talking to interfacesâ??and interfaces are talking back. Now we need to ensure those interfaces can converse effectively, thoughtfully, and naturally. Preston So introduces us to the exciting new frontier of voice content design, and the questions that designers, content strategists, and engineers need to answer in order to build richly structured, inclusive communication with the powerful medium of voice.